HEALTHCARE WORKER-PATIENT RELATIONSHIPS IN PULMONOLOGY PRACTICE - L. Yu. Palmova; M. E. Guryleva (Туберкулез и болезни лёгких)
The paper considers doctor-patient relationships, compliance in routine practice, and the psychological characteristics of patients with pulmonary diseases.